2002
DOI: 10.1103/physreve.66.031503
|View full text |Cite
|
Sign up to set email alerts
|

Merging of α and slow β relaxation in supercooled liquids

Abstract: Dielectric relaxation spectroscopy (1 Hz -20 GHz) has been performed on supercooled glassformers from the temperature of glass transition (Tg) up to that of melting. Precise measurements particularly in the frequencies of MHz-order have revealed that the temperature dependences of secondary β-relaxation times deviate from the Arrhenius relation in well above Tg. Consequently, our results indicate that the β-process merges into the primary α-mode around the melting temperature, and not at the dynamical transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
53
2
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 30 publications
(28 reference statements)
9
53
2
1
Order By: Relevance
“…Therefore, we can reliably deduce only that the activation energy of the ␤ relaxation is higher for the ultraviscous liquid than for the glassy state, but not exactly how much higher. Fujima et al 34 have observed a similar feature in the plot for D-sorbitol. They have shown it as a plot of the symmetric broadening parameter for the ␤ relaxation against 1 / T in Although a detailed resolution of the spectra for D-sorbitol has supported their findings, 34 we investigate if the features observed here could be seen as an artifact of local temperature change in the sample as a result of structural relaxation during the course of measurements.…”
Section: -4supporting
confidence: 50%
See 2 more Smart Citations
“…Therefore, we can reliably deduce only that the activation energy of the ␤ relaxation is higher for the ultraviscous liquid than for the glassy state, but not exactly how much higher. Fujima et al 34 have observed a similar feature in the plot for D-sorbitol. They have shown it as a plot of the symmetric broadening parameter for the ␤ relaxation against 1 / T in Although a detailed resolution of the spectra for D-sorbitol has supported their findings, 34 we investigate if the features observed here could be seen as an artifact of local temperature change in the sample as a result of structural relaxation during the course of measurements.…”
Section: -4supporting
confidence: 50%
“…Fujima et al 34 have observed a similar feature in the plot for D-sorbitol. They have shown it as a plot of the symmetric broadening parameter for the ␤ relaxation against 1 / T in Although a detailed resolution of the spectra for D-sorbitol has supported their findings, 34 we investigate if the features observed here could be seen as an artifact of local temperature change in the sample as a result of structural relaxation during the course of measurements. A possible local increase in the temperature as a result of structural relaxation at T Ͻ T g , would raise f m and would therefore increase the slope of the log͑f m,␤ ͒ against 1 / T plot at T near T g , but here a decrease is observed in Fig.…”
Section: -4supporting
confidence: 50%
See 1 more Smart Citation
“…In subsequent years, it became a key tool for estimating the so-called dynamic crossover temperature T B between two dynamic domains. 7,[18][19][20][21][22][23][24] It was shown that at least two VFT equations are desired for describing pre-vitrificational slowing down in a broader range of temperatures. The temperature T B has been also recognized as a milestone in the way on approaching T g since a lot of exceptional phenomena disclose there, for instance: [18][19][20][21][22][23][24][25][26][27][28][29][30][31] (1) the loss of ergodicity as predicted by mode-coupling theory (MCT), (2) increasing broadening of the structural relaxation time distribution, (3) a marked change in temperature dependence of the nanopore unoccupied volume radius, (4) splitting of the high temperature relaxation into the primary and secondary relaxation times, (5) orientational-translational decoupling, (6) for a broad set of supercooled systems τ (T B ) = 10 −7±1 s or η(T B ) ≈ 10 3 P-i.e., it is near-universal, (7) τ (T B , P B ), η(T B , P B ) = const for a given glass former, (8) it is believed that the dynamical crossover is closely related to the onset of caging and appearing of dynamical heterogeneities, (9) the coefficient D T in the VFT equation almost always increases on crossing to the dynamical domain in the immediate vicinity of T g .…”
Section: Introductionmentioning
confidence: 99%
“…22 These facts are worth stressing because the dynamic crossover is sometimes linked to the "FS" crossover. 32 However, there are fundamental weak points in the discussion employing the "Stickel analysis" carried out so far, namely: (1) an impressive number of papers discussing the dynamical crossover explores only the "formal" plot ϕ T vs. 1/T, or its pressure counterpart ϕ P = (dlog 10 τ /dP) −1/2 vs. P, without an attempt of finding a possible physical meaning hidden behind [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (2) the general validity of the VFT equation, underlying ϕ T (T) "Stickel" function, has been strongly questioned in recent years.…”
Section: Introductionmentioning
confidence: 99%